The Effect of Problem-Based Learning Model Increase The Creative Thinking Skill and Students Activities on Elementary School (Universitas Negeri Semarang, 2018)
The objective of this research is to know the effect of problem-based learning model towards creative thinking skill and students activity. The research was conducted on the social problem material. The research method was Quasi Experimental Design. The sampling technique was cluster random sampling. The data collected in the form of observation sheet instrument of students’ activity and instrument of creative thinking skill. Data were analyzed by using the independent t-test to test the comparasion or difference. In testing the effect, it used N-gain. The results of the research shows that there is a difference of influence of creative thinking skill; it is seen from the average of N-gain pretest and posttest of the students. The result of t-test in the experimental class reveals that the average score of pretest is 51.45, while in the posttest is 87.90, so the experimental group has an improvement of 26%. It is obtained tvalue is higher than ttable (2.917 > 2.000). The achievement of students activity in the experimental class improves, with the average score of observations that reaches very well criteria. The conclusion of this research is the problem-based learning model has an effect on the creative thinking skill and the students activity.